2019
DOI: 10.3389/fendo.2019.00515
|View full text |Cite
|
Sign up to set email alerts
|

Signal Transduction and Pathogenic Modifications at the Melanocortin-4 Receptor: A Structural Perspective

Abstract: The melanocortin-4 receptor (MC4R) can be endogenously activated by binding of melanocyte-stimulating hormones (MSH), which mediates anorexigenic effects. In contrast, the agouti-related peptide (AgRP) acts as an endogenous inverse agonist and suppresses ligand-independent basal signaling activity (orexigenic effects). Binding of ligands to MC4R leads to the activation of different G-protein subtypes or arrestin and concomitant signaling pathways. This receptor is a key protein in the hypothalamic regulation o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 149 publications
(225 reference statements)
0
23
0
5
Order By: Relevance
“…The confirmed mRNA sequences of the qPCR amplicons indicated that all four salmon mc4r genes are not pseudogenes. The Atlantic salmon showed wellconserved seven hydrophobic transmembrane domains as well as one putative disulfide bond, within the ECL3 for Mc4ra1 (Cys274 and Cys280) and Mc4rb2 (Cys275 and Cys281), as described for human MC4R (Cys271 and Cys277) (Chai et al, 2005;Chapman et al, 2010;Heyder et al, 2019). Even though Cys are also present in the primary sequence of Mc4ra2 and Mc4rb1, a disulfide bond was not present in the predicted tertiary structure in PyMOL.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The confirmed mRNA sequences of the qPCR amplicons indicated that all four salmon mc4r genes are not pseudogenes. The Atlantic salmon showed wellconserved seven hydrophobic transmembrane domains as well as one putative disulfide bond, within the ECL3 for Mc4ra1 (Cys274 and Cys280) and Mc4rb2 (Cys275 and Cys281), as described for human MC4R (Cys271 and Cys277) (Chai et al, 2005;Chapman et al, 2010;Heyder et al, 2019). Even though Cys are also present in the primary sequence of Mc4ra2 and Mc4rb1, a disulfide bond was not present in the predicted tertiary structure in PyMOL.…”
Section: Discussionmentioning
confidence: 93%
“…In general, for human MC4Rs, the pocket of aspartic acid Asp122/126 in TMHIII and basic histidine (His) 264 residues in TMHVI (Metz et al, 2006;Chapman et al, 2010;Wen et al, 2017;Heyder et al, 2019) along with ECL2 and ECL3 (Tao, 2010) are essential for ligand binding. β-MSH has been shown to the have the highest affinity to human MC4R, followed by α-MSH and ACTH (Tao, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This hints to the importance of the G q/11 pathway, as a strong bias towards PLC activation of V103I might play a part in its suggested protective role against obesity [30][31][32][33][34]. The rare mutation H158R is located in the ICL2, which is part of the G protein binding site and has been postulated to be important for G q/11 coupling as well [64]. The observed gain-of-function in this pathway therefore suggests functional relevance of this position.…”
Section: Signaling Bias Towards G Q/11 Of Two Mutations When Stimulatmentioning
confidence: 85%
“…In contrast to most of the other class A GPCRs, the MC4R EL2 has been reported to only consist of three to four amino acids (e.g., [ 48 ]), which has been recently confirmed by the inactive MC4R crystal structure [ 21 ] ( Figure 2 and Figure 4 ). Usually, in class A GPCRs, the EL2 comprises ~10–30 amino acids and is located centrally above the transmembrane helical bundle.…”
Section: Specific Features In the Mc4r Sequence And Structure Linkmentioning
confidence: 87%
“…This is also of importance because obesity is related to different comorbidities, such as type 2 diabetes mellitus or cardiovascular disease [ 47 ]. To date, approximately 165 missense mutations in 129 different residues have been reported [ 48 ]. Several of these pathogenic MC4R mutations have been observed to cause biased signaling through the MC4R by forcing preference for a specific signaling pathway [ 39 , 49 , 50 , 51 , 52 ] (reviewed in [ 35 ]).…”
Section: The Melanocortin-4 Receptormentioning
confidence: 99%